Eternal bonds / Fatin Zaida Zaidi - Zaidi, Fatin Zaida (Academy of Language Studies, 2024)
I treasure each moment, each fleeting embrace, Through twilight and dawn, your steadfast grace, My midnight whispers, never left unheard, Our conversations, like dreams, gently stirred.